KERAGAMAN TANAMAN SENGON DI JAWA BARAT - M. Hadad EA; Agus Ruhnayat; Reza Adella (PERHIMPI (Indonesian Association of Agricultural Meteorology), 1990)
Abstract is available in the full text (pdf format)